Efektivitas Penerapan Modified Early Obstetric Warning System (MEOWS) untuk Menurunkan Morbiditas pada Ibu Postpartum - Faidana Yaumil Syifa; Ade Sriwahyungsih (Jurnal Medicare, 2025)
Based on the 2020 Population Census, Indonesia's maternal mortality rate (MMR) reached 189 per 100,000 live births, ranking third highest in ASEAN. The high MMR is closely related to increased maternal morbidity. Early detection is a key strategy to reduce morbidity, one of which is by using the Modified Early Obstetric Warning System (MEOWS). This tool is effective in predicting morbidity risk and the length of postpartum care. This study is a literature review analyzing the effectiveness of MEOWS in reducing postpartum maternal morbidity. Articles were retrieved from electronic databases including PubMed, Sage Journal, Science Direct, and Proquest using the keywords “postpartum,” “modified early obstetric warning system,” and “maternal morbidity.” Out of 665 articles found, 6 were selected based on inclusion and exclusion criteria. The review results showed that MEOWS is effective in predicting postpartum maternal morbidity, with sensitivity reaching up to 99.3% and specificity of 93.5%.